One-pot synthesis of silver-modified sulfur-tolerant anode for SOFCs with an expanded operation temperature window - Qu, J.; Wang, Wei; Yang, T.; Chen, Y.; Shao, Zongping (John Wiley & Sons, Inc., 2017)
© 2017 American Institute of Chemical Engineers To develop solid oxide fuel cells (SOFCs) capable of operating on sulfur-containing practical fuels at intermediate temperatures, further improvement of the sulfur tolerance of a Ni + BaZr 0.4 Ce 0.4 Y 0.2 O 3-δ (BZCY) anode is attempted through the addition of some metal modifiers (Fe, Co, and Ag) by a one-pot synthesis approach. The effects of these modifiers on the electrical conductivity, morphology, sulfur tolerance, and electrochemical activity of the anode are systematically studied. As a result, the cell with Ag-modified Ni + BZCY anode demonstrates highest power output when operated on 1000 ppm H 2 S-H 2 fuel. Furthermore, the Ag-modified anode displays much better stability than Ni + BZCY with 1000 ppm H 2 S-H 2 fuel at 600°C. These results suggest that the addition of Ag modifier into Ni + BZCY is a promising and efficient method for improving the sulfur tolerance of SOFCs. © 2017 American Institute of Chemical Engineers AIChE J, 63: 4287–4295, 2017.